PENGARUH PENGETAHUAN KEUANGAN, PENGALAMAN KEUANGAN, DAN SIKAP KEUANGAN TERHADAP PERILAKU KEUANGAN PADA PEGAWAI PEMERINTAH BPKAD DI KABUPATEN KEPULAUAN ARU - Kalorbobir, Yohana Magdalena; Temalagi, Selva (Jurnal Akuntansi Kompetif, 2025)
This study aims to examine the influence of financial knowledge, financial experience, and financial attitude on financial behavior among civil servants (ASN) at the Regional Financial and Asset Management Agency (BPKAD) in the Aru Islands Regency. Civil servants are expected not only to possess professional competencies but also to manage their personal finances wisely. The research employs a quantitative approach using a survey method, with questionnaires distributed to 38 ASN employees as research respondents. Data were analyzed using multiple linear regression to determine the relationship between the variables. The findings reveal that financial knowledge has a significant influence on financial behavior. However, financial experience and financial attitude do not have a significant partial influence. The study contributes theoretically by enriching the literature on financial behavior and practically by supporting the development of financial literacy among government employees. These results highlight the need for structured financial education programs to enhance the personal financial management capabilities of civil servants. Keywords: Financial Knowledge, Financial Experience, Financial Attitude, Financial Behavior, Government Employees